Simultaneous Effect on Debt and Managerial Ownership: Agency Theory Framework - Akhbar, Taufik (KINERJA, 2017)
This study aims to examine the debt policy and managerial ownership as tools to control the agency conflict. Debt policy and managerial ownership used in controlling agency conflicts have several considerations such as the risk of the company, the company's growth and the presence of institutional ownership in a company. The variables used in this study include earnings volatility as a measure of corporate risk, growth companies, managerial ownership, institutional ownership, debt policy, and total assets as a control. Furthermore, an analysis by means of regression models with simultaneous Two Stage Least Square method was used. The results found in this study stated that the risk factors, the growth of the company, as well as the existence of institutional ownership affect debt policy and managerial ownership control of the company within the framework of the agency conflict. This indicates that the use of policies to control the agency conflict must consider these three factors. Keywords: agency conflict, debt policy, managerial ownership